Visual Language of Javanese Script on Shoe Design as Cultural Identity - Purnomo, Cynthia Ayu; Mahanaim, Soteria Adia; Riva Lo, Fang-ying; Ardaniah, Viqi; Ardhianto, Peter (Institut Seni Indonesia Surakarta, 2021)
Various culture in Indonesia is slowly being forgotten by the majority, for people now uses another way of communication to deliver the message from one person to another. One of the examples that could see is the usage of Javanese script or usually called Hanacaraka. Therefore, studying the visual language of shoe design from Flymax Indonesia case study will help the public to understand how urgent creative cultural product is. This research uses qualitative research regarding the case study based on the in-depth interview through the owner of Flymax Indonesia and visual language analysis regarding the visuals. This study has implications for the creative industry practitioners in conveying visual language and impacting methods in developing creative products by including cultural elements in popular products. From Flymax study case, implementing cultural to modern shoes is to strengthen cultural identity, user identity, and local brand identity, moreover supporting local economic growth and cultural preservation.